A Foreign Investment Destination Risk Framework: Evaluating the Southern African Development Community Member States - Oberholzer, Merwe; Buys, Pieter (Acta Universitatis Lodziensis. Folia Oeconomica, 2024)
Potential investment risks need to be understood by an investor organisation, which implies that a host country’s environment plays a significant role in attracting foreign investment. This paper’s purpose was to propose a foreign investment risk conceptual framework to serve as a basis for evaluating the Southern African Development Community (SADC) Member States’ investment risk/attractiveness. Firstly, the most appropriate foreign investment risk indicators from the literature were identified to develop a foreign investment risk framework. Ten recent peer‑reviewed studies were used to identify the factors which drive investment risk in emerging markets. We developed a conceptual framework including 16 investment risk indicators grouped into four sections: (i) the business environment, (ii) related taxes on business operations, (iii) the economic environment, and (iv) the human and social environments. Secondly, a comparative analysis of the 16 SADC countries was performed, enabling the ranking of the countries in quadrants of investment risk/attractiveness. Data were downloaded from theGlobalEconomy.com (2022) website for six years, from 2015 to 2020. The literature suggests many investment risk indicators which are grouped differently by researchers to form a conceptual framework to evaluate investment risk. This study’s contribution is that the most popular/prevalent risk indicators were identified to develop the new proposed framework. Furthermore, evaluating the SADC region may also serve as an example of investment risk/attractiveness assessment of emerging markets or least‑developed countries. The practical implication of this paper is that the proposed framework enables transferability since potential investors may connect the fundamentals of this study with their own investigation.